The Ritual Background of the Dying God in Cyprus and Syro-Palestine - Robertson, Noel (Harvard theological review, 1982)
In Frazer's Golden Bough the leading instance of the central figure whom he called “the dying god” was Adonis, famous from Greco-Roman literature and art but firmly localized in Semitic Phoenicia, Syria, and Cyprus. Since Frazer wrote, his other Near Eastern instances have been so transformed by increasing knowledge that it can be doubted whether they severally belong to the same type or indeed whether any general type exists. Adonis has hardly shared in these discoveries and debates, for research has emphasized instead the large developments which overtook his worship within the Greco-Roman world. Most of this research does not bear at all on the origins of Adonis, but scholars have sometimes been so bemused by the Greek elements as to forget or deny the Semitic. Everything has been called into question at different times. Such features of his myth as the boar and the myrrh tree and the incest are discounted as Greek embroidery; his peculiar festival, with mourning women and miniature gardens of lettuce, is traced to the preoccupations of Greek urban society; even the Semitic derivation derivation of his name is disputed. This Greek exclusivism cannot be sustained. All accounts of Adonis' life and lineage, and all analogies for his worship converge in the Levant — not in a single site or land, but in Phoenicia, coastal Syria and Cyprus together, lands which from the Late Bronze Age onward display a distinctive common culture, above all with respect to religion. This is where Adonis is at home, and where we may look for evidence to explain the figure of the dying god.